Biogeochemical sulfur cycling during Cretaceous oceanic anoxic events: A comparison of OAE1a and OAE2. (4th February 2016) - Gomes, Maya L.; Hurtgen, Matthew T.; Sageman, Bradley B.
Abstract: Biogeochemical sulfur cycling has varied widely over geologic time, mainly in response to changes in primary productivity and organic carbon burial, volcanism, weathering, and evaporite deposition. Several of these processes are explicitly linked to discreet (<1.2 Ma) intervals of widespread organic carbon burial, termed oceanic anoxic events (OAEs). During the Cretaceous, there is a highly distinctive ~4‰ negative excursion in the sulfur isotope composition of seawater sulfate (δ 34 SSO4 ) that is bracketed by the two most prominent OAEs (OAE1a and OAE2). This excursion lasted for ~25 Ma and has been variously attributed to enhanced volcanism, changes in weathering, evaporite burial, and/or changes in modes of organic carbon remineralization. We present new high‐resolution carbon and sulfur isotope records from carbonate‐associated sulfate and pyrite for OAE1a and OAE2. OAE1a is characterized by a monotonic decrease in δ 34 SSO4 values. Both negative and positive δ 34 SSO4 excursions are associated with OAE2. To refine hypotheses for the observed changes in biogeochemical sulfur cycling associated with these events, we use a simple sulfur isotope box model. Both empirical and modeling results indicate that δ 34 SSO4 variability was dominated by input fluxes during OAE1a, whereas enhanced volcanism, weathering, and pyrite burial controlled δ 34 SSO4 records during OAE2. Our analysis supports the conclusion that Cretaceous marine sulfate concentrations were much lower than modern concentrations and indicates that increases in marine sulfate occurred at the onset of both events. We conclude that increases in marine sulfate from low background concentrations, in conjunction with other environmental characteristics, contributed to the development of OAEs. Key Points: Cretaceous oceanic anoxic events are linked with a negative excursion in sulfate sulfur isotopes Pyrite‐sulfur isotopes during OAEs indicate enhanced pyrite burial in oxygen‐depleted environments Increases in sulfate levels and pyrite burial link volcanism to the development of OAEs